Influence of Photosensitizer on Photodynamic Therapy for Peri-Implantitis: A Systematic Review - Thaís B. M. O. Schweigert; João P. R. Afonso; Renata K. da Palma; Iransé Oliveira-Silva; Carlos H. M. Silva; Elias Ilias Jirjos; Wilson Rodrigues Freitas Júnior; Giuseppe Insalaco; Orlando A. Guedes; Luís V. F. Oliveira (MDPI AG, 2024)
The treatment of peri-implantitis is challenging in the clinical practice of implant dentistry. With limited therapeutic options and drug resistance, there is a need for alternative methods, such as photodynamic therapy (PDT), which is a minimally invasive procedure used to treat peri-implantitis. This study evaluated whether the type of photosensitizer used influences the results of inflammatory control, reduction in peri-implant pocket depth, bleeding during probing, and reduction in bone loss in the dental implant region. We registered the study in the PROSPERO (International Prospective Register of Systematic Review) database. We searched three main databases and gray literature in English without date restrictions. In vivo randomized clinical studies involving individuals with peri-implantitis, smokers, patients with diabetes, and healthy controls were included. PDT was used as the primary intervention. Comparators considered mechanical debridement with a reduction in pocket depth as the primary outcome and clinical attachment level, bleeding on probing, gingival index, plaque index, and microbiological analysis as secondary outcomes. After reviewing the eligibility criteria, we included seven articles out of 266. A great variety of photosensitizers were observed, and it was concluded that the selection of the most appropriate type of photosensitizer must consider the patient's characteristics and peri-implantitis conditions. The effectiveness of PDT, its effects on the oral microbiome, and the clinical patterns of peri-implantitis may vary depending on the photosensitizer chosen, which is a crucial factor in personalizing peri-implantitis treatment.